Reliable and Secure Geocasting in VANETs - Prado Bernia, Antonio (Université d'Ottawa / University of Ottawa, 2012)
Current geocasting algorithms for VANETs are being designed to enable either private or reliable communications, but not both. Existing algorithms preserve privacy by minimizing the information used for routing, and sacrifice message delivery success. On the other hand, reliable protocols often store node information that can be used to compromise a vehicle's privacy. We have designed two private and reliable geocasting protocols for VANETs that ensure confidentiality. One is a probabilistic algorithm that uses direction-based dissemination, while the other is a deterministic algorithm that uses transmission-coverage dissemination. To preserve privacy, we create unlinkable and pseudonymous channels of communication with geocasting. For encryption and authentication, we use a public key technique. Our probabilistic forwarding model depends on message rate and cumulative payload, as well as the value of the angle of spreading of the direction-based scheme. To reduce message duplication, we apply dynamic traffic restriction and probabilistic forwarding techniques. The deterministic forwarding algorithm delays forwarding messages based on its uncovered transmission area after neighbouring nodes have broadcast the message. We prove that both algorithms ensure node privacy with appropriate message encryption security, and we ran simulations to demonstrate that both meet the message delivery requirements. From the gathered data, we observe that both algorithms behave differently depending on the scenario, with node density affecting the deterministic algorithm, while the angle of spreading does have a significant impact on the probabilistic protocol.
Keywords: VANET; Geocast; Privacy; Reliability; Probabilistic Forwarding; Deterministic Forwarding; Transmission-Coverage; Direction-Based